Estimation of Soil Loss in Three Agro-climatic Zones of Belagavi District, Karnataka Using USLE and GIS - and P.L. Patil, K. Prabhavathi, G.S. Dasog M.V. Manjunath, M. Korade (Journal of the Indian Society of Soil Science, 2017)
Estimating soil loss using Universal Soil Loss Equation (ULSE) and geographical information system (GIS) was attempted in three agro-climatic zones of Belagavi district in north Karnataka. The study area included one micro-watershed in each agro-climatic zone viz., Yadawad in northern dry zone (zone 3), Hukkeri in northern transitional zone (zone 8) and Khanapur in hilly zone (zone 9). Slope gradient map was prepared from SRTM-DEM and the R, K and LS factors in USLE were determined from the established equations. Information on conservation was obtained from field survey. Using a grid-based approach, soil loss map was prepared in GIS environment. The predicted soil loss varied among the agro-climatic zones. The soil loss was very low to low (< 10 t ha-1) in the entire Yadawad micro-watershed area, whereas, it was moderately high to high (15-40 t ha-1) in 32% of Hukkeri and 19% of Khanapur micro-watersheds due to slope and land use characteristics. Despite heavy rainfall in Khanapur watershed, the soil loss risk was more for Hukkeri watershed suggesting that factors other than rainfall played an important role in rendering the soil loss.